50th AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2012
DOI: 10.2514/6.2012-1270
|View full text |Cite
|
Sign up to set email alerts
|

Large Eddy Simulation of Supercritical Nitrogen Jets

Abstract: Within the development of a reliable numerical tool for the simulation of a whole rocket combustion chamber, real-gas thermodynamics have been implemented into two CFD codes, the in-house code INCA of the Institute of Aerodynamics and Fluid Mechanics at Technische Universität München and OpenFOAM, used by the Institute for Thermodynamics at Universität der Bundeswehr München. The present work, where Large Eddy Simulations (LES) are conducted for the transcritical injection of nitrogen, is part of the validatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 16 publications
0
31
0
Order By: Relevance
“…The cu-LIQUID AND ELECTRIC SPACE PROPULSION bic Peng Robinson (PR) equation of state (EoS) [20] has been used to describe the thermodynamic behavior of the §uid. As a part of the validation, both codes have already been successfully used to reproduce DNS results of Okong£o et al [21] for an inert, transitional, temporal mixing layer [22]. OpenFOAM has also been tested for trans-and supercritical nitrogen jets [17] and reproduced the experiments in good agreement.…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations
“…The cu-LIQUID AND ELECTRIC SPACE PROPULSION bic Peng Robinson (PR) equation of state (EoS) [20] has been used to describe the thermodynamic behavior of the §uid. As a part of the validation, both codes have already been successfully used to reproduce DNS results of Okong£o et al [21] for an inert, transitional, temporal mixing layer [22]. OpenFOAM has also been tested for trans-and supercritical nitrogen jets [17] and reproduced the experiments in good agreement.…”
Section: Introductionmentioning
confidence: 66%
“…As a part of the validation, both codes have already been successfully used to reproduce DNS results of Okong£o et al [21] for an inert, transitional, temporal mixing layer [22]. OpenFOAM has also been tested for trans-and supercritical nitrogen jets [17] and reproduced the experiments in good agreement. In the following, the numerical method used in both codes as well as the thermodynamic modeling are presented.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…They suggested that pseudovaporization in §uences the unsteady behavior of the cryogenic jet core. Zong and Yang [3] and Jarczyk and P¦tzner [6] conducted LES of cryogenic nitrogen jets under transcritical conditions. They showed that strong anisotropy of turbulence occurs in the initial mixing region owing to the large density strati¦cation between the injected and ambient §uids.…”
Section: Introductionmentioning
confidence: 99%